2022
DOI: 10.1590/s1984-29612022004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Eimeria spp. natural infection in sheep from northern Paraná, Brazil

Abstract: The present study aimed to perform an epidemiological and morphological identification of Eimeria infection in sheep in Brazil. Fecal samples from sheep were collected from 20 farms in northern Paraná, Brazil. An epidemiological questionnaire was used to evaluate the risk factors. Fecal samples containing oocysts per gram of feces (OoPG) ≥1000 were subjected to the modified Willis-Mollay method to perform oocyst identification. Sporulated oocysts were observed microscopically for morphological identification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(39 reference statements)
1
0
0
Order By: Relevance
“…In this study, lambs were 3.5 times more likely to be infected by coccidian parasites than adult sheep, indicating that age is one of the main factors influencing the occurrence of protozoasis in these ruminants (p = 0.037). In accordance with the result of the present study, other surveys conducted in Brazil, Ethiopia, Iran, and Nigeria have also reported a significantly higher prevalence of coccidiosis in lambs compared to adult sheep (p < 0.05) [70][71][72][73]. The high susceptibility of young animals is related to immunological aspects, with adults acquiring specific immunity against protozoa after initial exposure [74].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, lambs were 3.5 times more likely to be infected by coccidian parasites than adult sheep, indicating that age is one of the main factors influencing the occurrence of protozoasis in these ruminants (p = 0.037). In accordance with the result of the present study, other surveys conducted in Brazil, Ethiopia, Iran, and Nigeria have also reported a significantly higher prevalence of coccidiosis in lambs compared to adult sheep (p < 0.05) [70][71][72][73]. The high susceptibility of young animals is related to immunological aspects, with adults acquiring specific immunity against protozoa after initial exposure [74].…”
Section: Discussionsupporting
confidence: 91%
“…Young goats (age < 12 months) (95.9%) were more affected than adult goats (87.2%). In this study, age is one of the important risk factors for Eimeria infection in sheep (Carneiro et al 2022), however, another study reported that different age groups of animals were similarly exposed to Eimeria spp. (de Macedo et al 2020).…”
Section: Discussionmentioning
confidence: 78%
“…may be related to physiological factors such as due to stress, reduced immune system performance during pregnancy, cyclic parturition, and lactation, and its natural bodily resistance to parasites declines (Owusu et al 2016). However, males experience infection more frequently than females (Carneiro et al 2022). Male animals may be more susceptible to infections because of immunosuppression brought on by increased plasma levels of androgens hormone, particularly testosterone, during the reproductive season (Souza et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of coccidiosis, a parasitic infestation of the intestines, wet weather is known to promote incidences in livestock (Lopes et al, 2013). The analysis of risk factors showed that intensive rearing, no rotation of pasture, dirt, and slatted floors, and age up to 12 months were associated with infection (Carneiro et al, 2022).…”
Section: Introductionmentioning
confidence: 99%